The Effectiveness of Khan Academy as a Science Learning Support to Improve Student’s Mastery of Skills : Literature Review - Putri, Angelina Amalia (Journal of Environmental and Science Education, 2021)
This article aims to analyze the effectiveness of using the Khan Academy platform as a support for science learning during the Covid-19 Pandemic to improve students' mastery of online learning skills. Online learning is one of the impacts caused by the spread of Covid-19 in the field of education. This condition causes teachers to use digital technology such as platforms to support the learning process. The integration of Khan Academy in science learning is a breakthrough in delivering learning materials that are in accordance with the applicable curriculum with consideration of material from teachers that is applied online. In this case, the teacher can designate the material according to the mastery of the skills students have. Then students can carry out activities to analyze video tutorials, work on practice questions to do practicum according to the instructions in Khan Academy. Teachers and parents can also monitor and supervise the activities, abilities and mastery of students' material. Based on the literature review, Khan Academy helps in classroom management, practicum activities through video tutorials, and practice questions and activity monitoring as an effective student progress report.